PENGARUH ATMOSFER TOKO DAN EMOSI POSITIF TERHADAP PEMBELIAN IMPULSIF MAHASISWA MANAJEMEN FEB UNIVERSITAS HALU OLEO KENDARI - Dzulfikri Azis Muthalib (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the effect of online store atmosphere and positive emotions on impulsive buying among students of the Management Department, Faculty of Economics and Business, Universitas Halu Oleo Kendari, who actively engage in online shopping. This research employs a quantitative approach with a causal research design. Data were collected through an online questionnaire using a five-point Likert scale from 92 respondents selected through purposive sampling. Data analysis was conducted using multiple linear regression with SPSS version 26. The results indicate that online store atmosphere has a positive and significant effect on impulsive buying. Positive emotions also have a positive and significant effect on impulsive buying and demonstrate a more dominant influence compared to online store atmosphere. Simultaneously, online store atmosphere and positive emotions significantly affect impulsive buying. These findings suggest that a well-designed digital shopping environment can stimulate positive emotions, which in turn encourage impulsive buying behavior. This study contributes theoretically to the literature on e-commerce-based consumer behavior.